Pemberdayaan Taman Pendidikan Al-Qur’an (TPA) Sebagai Sarana Pembinaan dan Pembentukan Karanter Santri (Pengabdian di TPQ Al-Ikhwah Lumandi Palopo): Pemberdayaan Taman Pendidikan Al-Qur’an (TPA) Sebagai Sarana Pembinaan dan Pembentukan Karanter Santri (Pengabdian di TPQ Al-Ikhwah Lumandi Palopo) - S.AN., M.Si, Seriyanti (IKATAN ALUMNI DOSEN MAGANG KEMENRISTEKDIKTI TAHUN ANGKATAN 2017, 2022)
Al-Ikhwah Lumandi Al-Qur'an Education Park is one of the centers for religious character education for the current generation, in Palopo City. The presence of the Al-Ikhwah TPA is currently a solution for the community, especially for parents in the Griya Lumandi housing complex. With the Al-Ikhwa TPA, of course, it can help parents in religious character education for their children from an early age. Based on the TKA/TPA/TQA Management Management Book published by LPPTKA BKPRMI 2021 Al-Ikhwah Lumandi TPA is managed using the Qur'anic reading and writing learning method using the Iqro book. (TPA as) a means of Guiding and Formation of Santri character.